Crime and Fear in Public Places Towards Safe, Inclusive and Sustainable Cities - Ceccato, Vania; Nalla, Mahesh K. (Routledge Studies in Crime and Society, 2020)
No city environment reflects the meaning of urban life better than a public place does. A public place, whatever its nature - a park, a mall, a train platform or a street corner - is where people pass by, meet each other and at times become a victim of crime. With this book, we submit that crime and safety in public places are not issues that can be easily dealt with within the boundaries of a single discipline. The book aims to illustrate the complexity of patterns of crime and fear in public places with examples of studies on these topics contextualized in different cities and countries around the world. This is achieved by tackling five crosscutting themes: the nature of the city's environment as a backdrop for crime and fear; the dynamics of individuals' daily routines and their transit safety; the safety perceptions experienced by those who are most in fear in public places; the metrics of crime and fear; and finally, examples of current practices in promoting safety. All these original articles contribute to our quest for safer, more inclusive, resilient, equitable and sustainable cities and human settlements aligned to the Global 2030 Agenda for Sustainable Development.